Associação da Aptidão Física e dos Conhecimentos Alimentares com o IMC de crianças/jovens - Filipe Azevedo Ferreira (2018)
Objective: The objective of this study is to establish a relationship between physical fitness and eating skills with students' BMI.Material and Methods: The sample of the present study consists of 92 students, 54 female and 38 male, all belonging to Felgueiras and aged between 12 and 16 years old. The height (in cm) of the students was measured through a portable stadiometer (SECA 217). The weight (in kg) and % MG (total, trunk, upper and lower limbs) were evaluated by the Tanita BC545 electronic scale. The BMI was calculated using the formula weight / height (kg / m²). To describe the prevalence of overweight or obese subjects in the sample, the reference values suggested by McCarthy et al. (2006) and Cole & Lobstein (2012). For the evaluation of physical fitness, the Fitnessgram test battery was used, in particular the 20-Meter PACER Test for the evaluation of cardiovascular fitness. The nutritional and food knowledge questionnaire (QCNA) was used to collect the food knowledge data. Data analysis was performed using SPSS (version 24) (IBM Corporation, 2016). Absolute (n) and relative (%) frequencies were used in the description of the categorical variables, and the continuous variables were calculated as means (M) and standard deviations (SD). The relationship between variables was studied with the T-test, in the case of the comparison of two groups, after the distribution normality (Kolmogorov-Smirnov test) and the homogeneity of variances (Levene test) were verified.Results: Males have a positive result on abdominal strength, arms extension and aerobic fitness test; on the other hand, has a negative result on the flexibility of the right and left legs, with higher results in female students in these two parameters. Older students had lower abdominal strength, but more flexibility of the right and left legs. Knowledge about the diet-disease relationship has an association in increased abdominal strength and right leg flexibility. Finally, students with higher BMI indexes, configured by the definition of Cole and Lobstein (2012), present worse results in the aerobic fitness test.Conclusion: This study established statistically positive relationships between BMI and physical fitness. Regarding the relationship between BMI and dietary knowledge, some consistency was observed when comparing the students studied with the Cole & Lobstein (2012) BMI cut-offs, since here we were able to demonstrate that those with a higher BMI obtained worse responses in the QCNA, in the part of the diathetic recommendations and in the relation diet-illness, compared to the ones of low BMI.